Cultura associada de feijão e milho: VI — Efeito do espaçamento entre covas do milho - Geraldo Antônio, Geraldo Antônio; Candido da Silva, Corival; Vieira, Clibas; Chagas, José Mauro (Revista Ceres, 2025)
A study was carried out at Coimbra and Ponte Nova, state of Minas Gerais, to determine the effects of distance between the hills of maize on the yields of maize and beans (Phaseolus vulgaris L.) in associated cropping. The maize treatments were 0.25, 0.50, 0.75, and 1.00 m between hills, with 1, 2, 3, and 4 plants per hill, respectively, in rows 1.00 m apart. Beans were planted within the maize rows in the «rainy» season and in two rows between those of maize in the «dry» season. No significant differences were found at either locality among maize yields nor among bean yields within planting season.